Epidemiology and clinical characteristics of Epstein-Barr virus infection among children in Shanghai, China, 2017-2022 - Ye, Zhicheng; Chen, Luxi; Zhong, Huaqing; Cao, Lingfeng; Fu, Pan; Xu, Jin (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To investigate the epidemiology and infectious characteristics of Epstein-Barr virus (EBV) infection among children in Shanghai, China from 2017 to 2022. Methods: We conducted a retrospective analysis of 10,260 inpatient patients who were subjected EBV nucleic acid testing from July 2017 to December 2022. Demographic information, clinical diagnosis, laboratory findings, etc were collected and analyzed. EBV nucleic acid testing were performed by real-time PCR. Results: A total of 2192 (21.4%) inpatient children were EBV-positive, with the average age of 7.3 ± 0.1 y. EBV detection was stable from 2017 to 2020 (26.9 30.1%), but showed essential decreases in 2021 (16.0%) and 2022 (9.0%). EBV was highest (>30%) detected from three quarters (Q) including 2018-Q4, 2019-Q4 and 2020-Q3. There were 24.5% of EBV coinfection with other pathogens, including bacteria (16.8%), other viruses (7.1%) and fungi (0.7%). EBV viral loads increased when coinfecting with bacteria ((142.2 ± 40.1) ×104/mL) or other viruses ((165.7 ± 37.4) ×104/mL). CRP significantly increased in EBV/fungi coinfection, while procalcitonin (PCT) and IL-6 showed remarkable increases in EBV/bacteria coinfection. Most (58.9%) of EBV-associated diseases belonged to immune disorders. The primary EBV-related diseases were systemic lupus erythematosus (SLE, 16.1%), immunodeficiency (12.4%), infectious mononucleosis (IM, 10.7%), pneumonia (10.4%) and Henoch-schonlein purpura (HSP, 10.2%). EBV viral loads were highest ((233.7 ± 27.4) × 104/mL) in patients with IM. Conclusions: EBV was prevalent among children in China, the viral loads increased when coinfecting with bacteria or other viruses. SLE, immunodeficiency and IM were the primary EBV-related diseases.